Pengabdian Mahasiswa KKN Melalui Program Bimbingan Belajar Siswa TK-SD Desa Puput - Khasana, Ervina Putri Winda Ari; Veleza, Finki; Pebrianti, Della (LP2M IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2025)
This community service aims to increase the learning interest of kindergarten and elementary school students in Puput Village through a tutoring program. The problem faced is the low motivation and learning interest of students. The community service method used is descriptive qualitative research with observation and documentation study. The observation results show that a tutoring program is needed to increase students’ learning interest. Therefore, KKN IAIN SAS Bangka Belitung students implemented a free tutoring program using the BCM (Learning, Storytelling, Singing) method. As a result, the tutoring program successfully increased students’ learning interest. This can be seen from the monitoring and evaluation results which show that students can maintain a good understanding of the material. In conclusion, the tutoring program is able to be a solution to increase the learning interest of kindergarten and elementary school students in Puput village.